How effective is undergraduate palliative care teaching for medical students? A systematic literature review - Jason W Boland; Jane Gibbins; Megan E L Brown; Gabrielle M Finn; Angelique Duenas (BMJ Open)
Objectives To evaluate the effectiveness of palliative care teaching for undergraduate medical students.Design A systematic review was prepared according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance. Screening, data extraction and quality assessment (mixed methods and Cochrane risk of bias tool) were performed in duplicate.Data sources Embase, MEDLINE, PsycINFO, Web of Science, ClinicalTrials.gov, Cochrane and grey literature in August 2019. Studies evaluating palliative care teaching interventions with medical students were included.Results 1446 titles/abstracts and 122 full-text articles were screened. 19 studies were included with 3253 participants. 17 of the varied methods palliative care teaching interventions improved knowledge outcomes. The effect of teaching on clinical practice and patient outcomes was not evaluated in any study.Conclusions The majority of palliative care teaching interventions reviewed improved knowledge of medical students. The studies did not show one type of teaching method to be better than others, and thus no ‘best way’ to provide teaching about palliative care was identified. High quality, comparative research is needed to further understand effectiveness of palliative care teaching on patient care/clinical practice/outcomes in the short-term and longer-term.PROSPERO registration number CRD42018115257.